2006
DOI: 10.1177/147323000603400309
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-II Receptor Antagonist Alleviates Non-alcoholic Fatty Liver in KKAy Obese Mice with Type 2 Diabetes

Abstract: We examined the effects of the angiotensin-II receptor antagonist candesartan on non-alcoholic fatty liver (NAFL) and circulating adiponectin concentrations in KKAy obese mice with type 2 diabetes mellitus. The KKAy mice were randomly assigned to receive either candesartan at a once-daily dose of 10 mg/kg (n = 5) or placebo (n = 5). The differences in liver weight, histological evaluation of hepatic lipid infiltration, serum adiponectin concentration and hepatic adiponectin mRNA levels between the two groups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Prior to Res intervention, KKAy mice present with weight gain and increases in TG, TC, and LDL-C levels compared to C57BL/6 J mice, moreover, after 12 weeks, non-treated KKAy mice developed severe oxidative stress and metabolic disorders in liver, leading to the unfavorable decreases of liver enzymes such as GPx, which is consistent with previous study supporting these mice as proper animal model for investigation of lipid metabolic disorders [18]. In our study, we investigated the effect of Res on lipid metabolism via dietary Res treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Prior to Res intervention, KKAy mice present with weight gain and increases in TG, TC, and LDL-C levels compared to C57BL/6 J mice, moreover, after 12 weeks, non-treated KKAy mice developed severe oxidative stress and metabolic disorders in liver, leading to the unfavorable decreases of liver enzymes such as GPx, which is consistent with previous study supporting these mice as proper animal model for investigation of lipid metabolic disorders [18]. In our study, we investigated the effect of Res on lipid metabolism via dietary Res treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Candesartan increases circulating adiponectin concentration in human [9,18] and in diabetic mice [11]. Candesartan also increases adiponectin mRNA in fat tissue in hypertensive rat [12].…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that candesartan increases circulating adiponectin concentrations in human [15] and in diabetic mice [16]. Candesartan also increases adiponectin mRNA of fat tissue in hypertensive rats [17].…”
Section: Introductionmentioning
confidence: 97%